AN EMPIRICAL INVESTIGATION INTO THE DRIVERS OF SECONDARY SCHOOL FUNDING DISPARITIES AND THEIR EFFECTS ON SCHOOL PERFORMANCE: EVIDENCE FROM SELECTED PUBLIC SECONDARY GENERAL EDUCATION SCHOOLS IN THE NORTH WEST REGION OF CAMEROON - Christopher, Millah; Fabien, Sundjo (Journal of Education and Practice, 2019)
Purpose: School funding has been and remains a source of worry to governments of many countries in the world. The government of Cameroon in an attempt to attend to this worry spends huge financial resources each year as funding to the school system. This study attempted to investigate into the appropriateness of government funding to public secondary general education schools in Cameroon, using the North West Region as a case study. Specifically, the study aimed at: (a) investigating the causes of funding disparities between schools, (b) scrutinizing the effects of funding on school performance, and (c) elucidating the grass root perspectives on appropriate measures to enhance funding to schools. Methodology: The study made use of the stratified random sampling technique to select a total of 115 schools, and data was collected using questionnaires. To ascertain the reliability of the instrument used, a pilot test was carried out. The data was analysed using both descriptive and inferential statistics. The probit and ordered logistic regression models were employed to test the hypotheses of the study. Findings: The findings from the study reveal among others that: (a) school enrolment, school needs, influence by some stakeholders and age of school all have significant effects on funding, (b) that funding in the form of infrastructure, running credits and staffing all affect school performance, and (c) that schools should be funded based on their actual needs. Contribution to policy, practice and policy: These results policy-wise suggest that funding to schools should take into consideration the enrolment, needs, and age of the school. Also, that adequate infrastructure, running credits and staff should be provided to schools since these affect academic performance.